When culture impacts health global lessons for effective health research - Banwell, Cathy; Ulijaszek, Stanley J.; Dixon, Jane (Academic Press, 2013)
Bringing the hard-to-quantify aspects of lived experience to analysis, and emphasizing what might be lost in interventions if cultural insights are absent, this book includes case studies from across the Asia and Pacific regions -Bangladesh, Malaysia, New Guinea, Indonesia, Thailand, South Korea, Australia, New Zealand, Tuvalu and the Cook Islands. When Culture Impacts Health offers conceptual, methodological and practical insights into understanding and successfully mediating cultural influences to address old and new public health issues.